Analysis of data normalization methods for photobleaching experiments - Antonenka, Mikhail V.; Halavatyi, Aliaksandr A.; Yatskou, Mikalai N.; Skakun, Victor V. (Journal of the Belarusian State University. Physics, 2017)
The research of normalization methods of fluorescence recovery after photobleaching experimental data for diffusion and chemical interactions models taking into account experimental features is performed. The comparison of data normalization methods is performed, and the classification of normalization methods based on biological system’s features is first proposed. The comparison of averaging experimental data method and averaging parameter estimation method is performed. It is shown that parameter estimation values averaging rather than experimental data values averaging leds to less biased estimates of biological system’s parameters.
Keywords: photobleaching; data analysis; simulation model; fluorescence recovery curve; normalization methods; diffusion